Occurrence of Salmonella and Campylobacter spp. in binavalve molluscs retailed in Selangor, Malaysia - Wong, S. J.; Abdul Aziz, Saleha (Veterinary Association Malaysia, 2010)
The consumption of raw or insufficiently cooked shellfish which include bivalve molluscs can cause food-borne diseases, such as salmonellosis and campylobacteriosis. This study was carried out to determine the occurrence of Salmonella and Campylobacter in blood cockles (Anadara granosa) and carpet clams (Paphia undulate) retailed in the markets. Twenty samples each of blood cockles and carpet clams (total 40 samples) were purchased from markets in Selangor. Sixteen or 40% of the samples were found positive for Salmonella species. The most frequently isolated serotypes were Sarmonella Corvalis (31.3%), followed by Salmonella Mikawasima and Salmonella Weltevreden (18.8% each), Salmonella Tennessee (12.5%), Salmonella Agona, Salmonella Pomona and Salmonella Typhimurium (6.3% each). Campylobacter was not isolated. This study shows the potential risk of acquiring salmonellosis from ingesting raw or undercooked blood cockles and carpet clams.